2021
DOI: 10.1111/1365-2745.13745
|View full text |Cite
|
Sign up to set email alerts
|

Browsing is a strong filter for savanna tree seedlings in their first growing season

Abstract: 1. Newly germinated seedlings are vulnerable to biomass removal but usually have at least 6 months to grow before they are exposed to dry-season fires, a major disturbance in savannas. In contrast, plants are exposed to browsers from the time they germinate, making browsing potentially a very powerful bottleneck for establishing seedlings.2. Here we assess the resilience of seedlings of 10 savanna tree species to topkill during the first 6 months of growth. Newly germinated seeds from four dominant African gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…These newly recruited species were Ehretia amoena (Boraginaceae), Commiphora glandulosa (Burseraceae), Gymnosporia senegalensis (Celastraceae), Euclea natalensis (Ebenaceae) , Grewia bicolor (Malvaceae), Ximenia caffra (Olacaceae), and Flueggea virosa (Phyllanthaceae)—a high diversity of families. While an increase in species post‐drought may lead to changes in succession and species composition, such gain of species can be ephemeral if resources are too scarce, competition with grasses is too high, or fires and herbivory remove juvenile plants (Archibald et al, 2021, Kraaij and Ward, 2006). While some individuals may have been suppressed by intense grazing and browsing before the drought and were therefore not visible (e.g., Ormocarpum trichocarpum ), others are likely to be recruits which have either seedbanks that respond to drought by germination with post‐drought rainfall (Figure S4c, Figure S4d) (Joubert et al, 2013, Tessema et al, 2017), or colonize post‐drought via a diverse range of dispersal, fire‐resistance, physiological, and anatomical functional traits.…”
Section: Discussionmentioning
confidence: 99%
“…These newly recruited species were Ehretia amoena (Boraginaceae), Commiphora glandulosa (Burseraceae), Gymnosporia senegalensis (Celastraceae), Euclea natalensis (Ebenaceae) , Grewia bicolor (Malvaceae), Ximenia caffra (Olacaceae), and Flueggea virosa (Phyllanthaceae)—a high diversity of families. While an increase in species post‐drought may lead to changes in succession and species composition, such gain of species can be ephemeral if resources are too scarce, competition with grasses is too high, or fires and herbivory remove juvenile plants (Archibald et al, 2021, Kraaij and Ward, 2006). While some individuals may have been suppressed by intense grazing and browsing before the drought and were therefore not visible (e.g., Ormocarpum trichocarpum ), others are likely to be recruits which have either seedbanks that respond to drought by germination with post‐drought rainfall (Figure S4c, Figure S4d) (Joubert et al, 2013, Tessema et al, 2017), or colonize post‐drought via a diverse range of dispersal, fire‐resistance, physiological, and anatomical functional traits.…”
Section: Discussionmentioning
confidence: 99%
“…This pressure has likely resulted in the evolution of tolerance of herbivory, as found here with individuals rapidly reaching survival size thresholds. Indeed, Archibald et al (2021) found that savanna tree species from drier systems (like V. karroo ) were tolerant of herbivory at younger ages than those from higher rainfall systems. This higher early survival was associated with lower rainfall particularly in palatable species, suggesting that herbivory, and not just aridity, is a selective force on this trait (Archibald et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Plant size thresholds of disturbance tolerance have been previously described for savanna tree species (Archibald et al, 2021), and so we hypothesise that CO 2 -stimulated growth increases the rate at which V. karroo seedlings reach a size threshold that allows them to survive herbivory. We hypothesise that increasing [CO 2 ] promotes belowground growth which aids recovery from browsing events, and decreases the likelihood of herbivory through reduced palatability and increased plant defences.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations